A Pedagogy of Alternatives: A Peace Education Comment on Mark Webb’s “Letter to Naomi Klein” - Reardon, Betty (In Factis Pax: Journal of Peace Education and Social Justice, 2008)
A major characteristic of the pedagogy of peace education as I have practiced it, is positing, assessing, and strategizing alternatives to the current world order, i.e. transforming reality. The pedagogy of alternatives derives from a basic assertion about the world order and the suffering that is integral to it. The assertion can be summed up in a phrase I’ve used trying to break through the sense of the inevitability of violence and injustice that so profoundly affects the thinking of citizens and is an ever present shadow over class discussions, the specter of realism. It is that specter that lies at the heart of Mark Webb’s critique of Naomi Klein’s The Shock Doctrine and her theory of disaster.